2018
DOI: 10.24052/jbrmr/v12is03/art-13
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between internal marketing and employee job satisfaction: A study from retail shops in Bangladesh

Abstract: A Retail store is now a prevalent concept in Bangladesh offering a wide range of necessity goods for household and daily living. Within the last one decade, superstores have developed positive perceptions among customer and this is the attractive business to many investors. As retail shop business is based on service sector, customer satisfaction and service delivery are keys to the success where having satisfied employees are essential. Hence, to achieve sustainable organizational development and higher organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 20 publications
5
38
0
7
Order By: Relevance
“…Our present research findings showed that academic staff developments significantly influence academic staff job satisfaction which confirmed the first hypothesis (H1) of the study and the results are reliable with past studies (Al-Makhadmah, 2015;Joung et al, 2015;Leong and Lam, 2016;Sarker and Ashrafi, 2018). Our second hypothesis (H2), the significant influence of rewards on academic staff job satisfaction is also supported and has results consistent with previous literature (Al-Makhadmah, 2015;Joung et al, 2015;Leong and Lam, 2016;Sarker and Ashrafi, 2018;Sohail and Jang, 2017). Reliable with the earlier literature findings (Al-Makhadmah, 2015;Lee and Wen-Jung, 2005;Leong and Lam, 2016;Sohail and Jang, 2017;Vallaster and de Chernatony, 2005) the present study supported the significant positive influence of internal communication on academic staff job satisfaction, i.e.…”
Section: Hypotheses Testing Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our present research findings showed that academic staff developments significantly influence academic staff job satisfaction which confirmed the first hypothesis (H1) of the study and the results are reliable with past studies (Al-Makhadmah, 2015;Joung et al, 2015;Leong and Lam, 2016;Sarker and Ashrafi, 2018). Our second hypothesis (H2), the significant influence of rewards on academic staff job satisfaction is also supported and has results consistent with previous literature (Al-Makhadmah, 2015;Joung et al, 2015;Leong and Lam, 2016;Sarker and Ashrafi, 2018;Sohail and Jang, 2017). Reliable with the earlier literature findings (Al-Makhadmah, 2015;Lee and Wen-Jung, 2005;Leong and Lam, 2016;Sohail and Jang, 2017;Vallaster and de Chernatony, 2005) the present study supported the significant positive influence of internal communication on academic staff job satisfaction, i.e.…”
Section: Hypotheses Testing Results and Discussionsupporting
confidence: 92%
“…= 0.218, P = <0.05) respectively (see Figure 2). Our present research findings showed that academic staff developments significantly influence academic staff job satisfaction which confirmed the first hypothesis (H1) of the study and the results are reliable with past studies (Al-Makhadmah, 2015;Joung et al, 2015;Leong and Lam, 2016;Sarker and Ashrafi, 2018). Our second hypothesis (H2), the significant influence of rewards on academic staff job satisfaction is also supported and has results consistent with previous literature (Al-Makhadmah, 2015;Joung et al, 2015;Leong and Lam, 2016;Sarker and Ashrafi, 2018;Sohail and Jang, 2017).…”
Section: Hypotheses Testing Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Ali (2016) focused his work on five dimensions comprising 26 items, applied to 305 employees of the Arab Academy of Science, Technology and Maritime Transport of Egypt, obtaining significant results in all its dimensions. Sarker and Ashrafi (2018) applied a tool that analyzed seven dimensions of internal marketing, with a target population of 250 retail store employees in the city of Dhaka, Bangladesh, where the significant effect on employee satisfaction was evident. In turn, Ramos (2018) in his research on this construct, considered the employees of 39 financial institutions in the Philippines, who used a five-dimensional composite instrument, obtaining results appropriate to the objectives set.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the performed literature overview on the topic of directions and tools of strategic marketing management of retail trade enterprises showed that this topic is thoroughly studied in the existing economic literature from the positions of traditional (e.g., consideration of the geographical factor and specific sectorial markets) and from the positions of new (e.g., innovational activity, usage of digital technologies and social media) directions and tools. The conceptual framework and applied aspects of strategic marketing management of retail trade enterprises are discussed in the papers of such experts as (Idowu & Ndidiamaka, 2018), (Krasyuk et al, 2017), (Kudyrko & Sevruk, 2016), , (Pavlikova & Čihovska, 2017), (Ramanathan et al, 2017), (Sarker & Ashrafi, 2018), (Sen & Ongsakul, 2017). In the work (Ahmad & Zabri, 2018) the authors show the necessity for managing knowledge for supporting high efficiency at retail trade enterprisesi.e., they focus on personnel marketing in the process of strategic marketing management by these enterprises.…”
Section: A Literature Reviewmentioning
confidence: 99%